What types of firms tend to be more innovative: A study on Germany - Stephan Brunow; Valentina Nafts (European Regional Science Association (ERSA), 2014)
Innovation is a key driver of technological progress and growth in a knowledge-based economy. There are various motives for individual firms to innovate: improving quality secures market leadership, introducing new products leads the firm into new markets, adopting new technologies could be seen as a catch-up strategy within an industry or an improvement of the firm's own products when the technology adopted is based on ideas from other industries. Firms can perform innovation activities in one or more of these areas or in none of them. We therefore raise the question of what types of firms tend to be more innovative, i.e. which firms innovate in more of these areas. For this purpose we employ firm-level survey data and combine it with administrative data from Germany's social security system. An ordered logit model is estimated using a variety of characteristics which describe the workforce employed and other firm-related variables, the regional environment where the firm is located, as well as industry and region fixed effects.
Keywords: J44; O31; R12; 330; firm innovation; labor diversity; ordered logit; regional economic environment